Spontaneous recovery of post-traumatic cerebrospinal fluid rhinorrhea following meningitis: A case report - çıtışlı, Veli; Kocaoğlu, Murat; Necan, Ceyda; İbrahimoğlu, Muhammet; Çeliker, Özkan; Baykara, Eyüp; Özdemir, Mevci; Acar, Feridun; Coşkun, Mehmet Erdal (International Journal of Health Sciences, 2015)
The aim of the present report was to present the patient with an anterior cranial base fracture who developed post-traumatic cerebrospinal fluid rhinorrhea, which recovered after onset of meningitis complication. A 26-year-old male patient who had a traffic accident one week ago was sent to our clinic because of his rhinorrhea persisting for 4 days. On cranial computed tomography, fracture of the left frontal skull base and sinus walls, a fracture line on temporal bone, parenchymal bleeding in the vicinity of the frontal sinus, subarachnoidal bleeding and left temporal extradural hematoma were detected. Then he underwent sinus wall repair and extradural hematoma was drained through bifrontal craniotomy. However, rhinorrhea persisted which resulted a deterioration in consciousness and he entered into a deep somnolent state. When his symptoms of meningitis became apparent, rhinorrhea of the patient disappeared. The patient transferred in intensive care unit and re-connected to a lumbar drainage system. On cerebral magnetic resonance imaging, regression of contrast-enhanced lesions localized in the left anterotemporal and frontal and in the regions lateral to the right trigon and medial to the right thalamus and in the right posteroparietal regions was observed. Despite repair of the anterior cranial fracture and lumbar drainage, rhinorrhea may persist. Herein, development of meningitis caused disappearing of rhinorrhea symptoms without any need for surgical intervention. Key words: Traumatic rhinorrhea, meningitis, smoking